An effort to increase waqf intention: The role of celebrity endorsers in social campaigns - Ratnasari, Ririn Tri; Timur, Yan Putra; Battour , Mohamed; Jamilu, Usman (al-Uqud : Journal of Islamic Economics, 2023)
The waqf is a fascinating research topic in Islamic economics (sharia). The massive potential for collecting waqf donations in Indonesia has yet to be maximised. Using celebrities as endorsers in waqf campaigns is one of the strategic solutions to increase people's intention to donate waqf. This study aims to identify the effect of the three attributes of celebrity endorsers on waqf intentions, with image and credibility as mediating variables. The research method used is quantitative, using SEM-PLS as an evaluation model. The respondents used were aged 17 years to> 65 years, with a total of 400 respondents. The variables of this study were measured using a 5-point Likert scale. This study concluded that all exogenous variables positively and significantly affected Nazhir's image and credibility. Likewise, the image and credibility variables of Nazhir are proven to positively and significantly affect the waqif's intention to donate waqf. In the IPMA analysis results, it was found that Nazhir's expertise and credibility were the variables with the highest level of importance and performance, in effect, the intention to donate. This research can be the basis for Nazhir's reference to being able to devise strategies for using celebrities as endorsers in supporting social campaigns by focusing on the expertise and knowledge of religion possessed by celebrity endorsers as the main criteria.